Parents’ resistance to standardized testing in a highly centralized system: The emergence of an opt-out movement in Israel - Sabag, Noy; Feniger, Yariv (Education Policy Analysis Archives, 2022)
This paper discusses the emergence of an opt-out movement in Israel led by parent associations at local and national levels. The protest targeted the use of a national standardized test, the Meitzav. Analyzing media coverage of this movement and informed by the theoretical arguments of the Advocacy Coalition Framework, the study suggests that by forming a coalition with the Teachers’ Union, parents proclaimed their right to a role in education policymaking in a highly centralized system. The coalition was successful in that it influenced the Ministry of Education to postpone the tests and form a special committee to reevaluate the national assessment policy. The Israeli case enhances our understanding of opt-out movements in different educational and institutional contexts.